Positive electrode mixture and secondary battery

By adding inorganic nanoparticles to electrode active materials, the agglomeration of carbon nanotubes is prevented, creating effective conductive paths and enhancing battery performance in high-performance applications.

JP7618615B2Active Publication Date: 2025-01-21TOYOTA BATTERY CO LTD +2
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2022042470
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2025-01-21
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Existing electrode composite materials used in high-performance applications like electric vehicles do not adequately support the required battery performance due to agglomeration of conductive fibrous carbon materials, leading to inefficient conductive paths.

Method used

Incorporating inorganic nanoparticles on the surface of electrode active materials to disperse conductive fibrous carbon materials, such as carbon nanotubes, within specific diameter and content ratios to form effective conductive paths without agglomeration.

Benefits of technology

The configuration enhances battery performance by ensuring the carbon nanotubes remain dispersed and form efficient conductive paths, improving overall battery efficiency and reducing reaction suppression.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618615000001
    Figure 0007618615000001
  • Figure 0007618615000002
    Figure 0007618615000002
  • Figure 0007618615000003
    Figure 0007618615000003
Patent Text Reader

Abstract

To ensure better battery performance.SOLUTION: An electrode mixture 50 contains an electrode active material 60 and a carbon nanotube CNT as a conductive fibrous carbon material 51. This electrode mixture 50 is configured to include inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to Positive electrode The present invention relates to an electrode mixture and a secondary battery. [Background technology]

[0002] Conventionally, as shown in, for example, Patent Document 1 and Patent Document 2, there are some that contain a conductive fibrous carbon material such as carbon nanotubes in an electrode mixture used to form an electrode active material layer. By adopting such a configuration, the conductive fibrous carbon material forms a conductive path. This makes it possible to ensure excellent battery performance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-220357 A [Patent Document 2] JP 2016-31922 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in applications requiring high levels of battery performance, such as electric vehicles, further improvements in performance are always being sought, and therefore the current situation is that the configurations of the above-mentioned conventional technologies do not necessarily satisfy the evolving requirements. [Means for solving the problem]

[0005] The electrode mixture that solves the above problems contains an electrode active material and a conductive fibrous carbon material, and also contains inorganic nanoparticles arranged on the surface of the electrode active material. According to the above configuration, a plurality of inorganic nanoparticles arranged on the surface of the electrode active material adhere to the conductive fibrous carbon material in the electrode mixture, so that the conductive fibrous carbon material is stretched. That is, the conductive fibrous carbon material in the electrode mixture is dispersed in a stretched state without agglomerating into lumps. As a result, the conductive fibrous carbon material in the electrode mixture can effectively form a conductive path for the electrode active material located in its vicinity. This can ensure excellent battery performance.

[0006] In the electrode mixture that solves the above problems, the inorganic nanoparticles preferably have an average diameter of 25 nm or more and 150 nm or less. According to the above-mentioned configuration, the inorganic nanoparticles arranged on the surface of the electrode active material are easily attached to the conductive fibrous carbon material contained in the electrode mixture, and this makes it possible to create a state in which the conductive fibrous carbon material in the electrode mixture effectively forms a conductive path for the electrode active material located in the vicinity thereof.

[0007] In the electrode composite that solves the above problems, when the content of the inorganic nanoparticles contained in the electrode composite is expressed as a weight percentage, it is preferable that the content of the inorganic nanoparticles is expressed by the following formula, y≦0.0106x−0.0033, where “y” is the content of the inorganic nanoparticles and “x” is the average diameter of the inorganic nanoparticles.

[0008] That is, by setting the content calculated using the above formula, it is possible to avoid a state in which the inorganic nanoparticles covering the surface of the electrode active material suppress the battery reaction. In addition, it is possible to create a state in which the inorganic nanoparticles arranged on the surface of the electrode active material effectively form a conductive path for the electrode active material located in the vicinity thereof. This can effectively improve the battery performance.

[0009] In the electrode composite that solves the above problems, it is preferable that the content of the conductive fibrous carbon material contained in the electrode composite is 0.5 wt % or more and 2.0 wt % or less, and the quantitative ratio of the inorganic nanoparticles to the conductive fibrous carbon material is 0.1 or more and 0.7 or less.

[0010] According to the above configuration, the ratio of the content of the inorganic nanoparticles to the content of the conductive fibrous carbon material can be suitably set. This makes it possible to efficiently create a state in which the conductive fibrous carbon material and the inorganic nanoparticles adhere to each other in the electrode mixture, and to avoid a state in which excess inorganic nanoparticles inhibit the battery reaction. As a result, the battery performance can be improved more effectively.

[0011] In the electrode mixture that solves the above problems, the diameter ratio of the inorganic nanoparticles to the conductive fibrous carbon material is preferably 1.1 or more and 3.5 or less. According to the above-mentioned configuration, the ratio of the particle size of the inorganic nanoparticles to the diameter of the conductive fibrous carbon material can be suitably set. This makes it possible to create a state in which the conductive fibrous carbon material and the inorganic nanoparticles are efficiently attached to each other in the electrode mixture. As a result, the battery performance can be improved more effectively.

[0012] In the electrode mixture that solves the above problems, the conductive fibrous carbon material is preferably carbon nanotubes. According to the above-mentioned configuration, the carbon nanotubes in the electrode mixture are attached to the inorganic nanoparticles arranged on the surface of the electrode active material, so that the carbon nanotubes are dispersed in an extended state in the electrode mixture without being aggregated into clumps. As a result, the carbon nanotubes can effectively form a conductive path for the electrode active material located in the vicinity thereof. This can improve the battery performance.

[0013] The electrode mixture that solves the above problems preferably contains at least one of alumina and lithium tungstate as the inorganic nanoparticles. According to the above-mentioned configuration, it is possible to effectively create a state in which the inorganic nanoparticles arranged on the surface of the electrode active material are attached to the conductive fibrous carbon material in the electrode mixture, and thus it is possible to improve the battery performance.

[0014] A secondary battery that solves the above problems is formed using any of the electrode mixtures described above. According to the above configuration, the performance of the secondary battery can be improved. The secondary battery that solves the above problem is a secondary battery formed using an electrode mixture containing an electrode active material and a conductive fibrous carbon material, the electrode mixture containing inorganic nanoparticles arranged on the surface of the electrode active material, and the inorganic nanoparticles have an average diameter of 25 nm or more and 150 nm or less, and when the content of the inorganic nanoparticles contained in the electrode mixture is expressed in weight percent, the content of the inorganic nanoparticles is represented by the following formula, y≦0.0106x-0.0033, where "y" is the content of the inorganic nanoparticles and "x" is the average diameter of the inorganic nanoparticles, the content of the conductive fibrous carbon material contained in the electrode mixture is 0.5 wt% or more and 2.0 wt% or less, the quantitative ratio of the inorganic nanoparticles / the conductive fibrous carbon material is 0.1 or more and 0.7 or less, and the diameter ratio of the inorganic nanoparticles / the conductive fibrous carbon material is 1.1 or more and 3.5 or less.

[0015] According to the above configuration, the performance of the secondary battery can be effectively improved. Effect of the Invention

[0016] According to the present invention, better battery performance can be ensured. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a perspective view of a secondary battery. [Diagram 2] FIG. [Diagram 3] FIG. 2 is a side view of the secondary battery. [Figure 4] FIG. 2 is an image diagram of an electron microscope photograph showing an electrode active material and a conductive fibrous carbon material contained in an electrode mixture. [Diagram 5] FIG. 2 is an image of an electron microscope photograph showing an electrode active material and a conductive fibrous carbon material located in the vicinity thereof. [Figure 6]FIG. 1 is an image of an electron microscope photograph showing an electrode active material having inorganic nanoparticles disposed on the surface. [Figure 7] FIG. 2 is a schematic diagram of an electrode active material, a conductive fibrous carbon material, and inorganic nanoparticles contained in an electrode mixture. [Figure 8] FIG. 1 is an image of an electron microscope photograph of an electrode active material having no inorganic nanoparticles on the surface. [Figure 9] FIG. 2 is a schematic diagram showing an electrode active material and a conductive fibrous carbon material in an electrode mixture that does not contain inorganic nanoparticles. [Figure 10] FIG. 2 is an image of an electron microscope photograph showing an electrode active material having no inorganic nanoparticles on its surface and a conductive fibrous carbon material located in the vicinity thereof. [Figure 11] FIG. 1 is an image of an electron microscope photograph showing an electrode active material and a conductive fibrous carbon material in an electrode mixture that does not contain inorganic nanoparticles. [Figure 12] 1 is a table showing test results regarding the ratio of inorganic nanoparticles to carbon nanotubes. [Figure 13] 1 is a graph showing test results regarding the ratio of inorganic nanoparticles to carbon nanotubes. [Figure 14] 1 is a table showing test results regarding the diameter ratio of inorganic nanoparticles to carbon nanotubes. [Figure 15] 1 is a graph showing test results regarding the diameter ratio of inorganic nanoparticles to carbon nanotubes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of an electrode mixture for use in a secondary battery will be described with reference to the drawings. 1, the secondary battery 1 includes an electrode assembly 10 in which a positive electrode 3, a negative electrode 4, and a separator 5 are integrated, and a case 20 that houses the electrode assembly 10. The secondary battery 1 of this embodiment has a configuration as a lithium ion secondary battery in which the electrode assembly 10 in the case 20 is impregnated with a non-aqueous electrolyte solution (not shown).

[0019] More specifically, in the secondary battery 1 of this embodiment, the positive electrode 3, the negative electrode 4, and the separator 5 are laminated with a sheet-like outer shape. Then, by winding up the laminate of the positive electrode 3, the negative electrode 4, and the separator 5, an electrode body 10 is formed in which the positive and negative electrodes and the separators 5 are alternately arranged in the radial direction with the separator 5 sandwiched between the positive electrode 3 and the negative electrode 4.

[0020] The case 20 of this embodiment includes a case body 21 having a flat, substantially rectangular box shape, and a lid member 22 that closes an open end 21x of the case body 21. The electrode body 10 of this embodiment has a flat outer shape that corresponds to the box shape of the case 20.

[0021] More specifically, as shown in FIG. 2, in the secondary battery 1 of this embodiment, the positive electrode 3 and the negative electrode 4 each have a configuration as an electrode sheet 35 including a current collector 31 having a sheet-like outer shape and an electrode active material layer 32 laminated on this current collector 31.

[0022] Specifically, for the electrode sheet 35P for the positive electrode 3, a composite paste 37P containing a lithium transition metal oxide serving as a positive electrode active material is applied onto a substrate 36P made of aluminum or the like that constitutes the positive electrode current collector 31P. For the electrode sheet 35N for the negative electrode 4, a composite paste 37N containing a carbon-based material serving as a negative electrode active material is applied onto a substrate 36N made of copper or the like that constitutes the negative electrode current collector 31N. Furthermore, each of these composite pastes 37P and 37N contains a binder. In the secondary battery 1 of this embodiment, the composite pastes 37P and 37N are dried to form the corresponding positive electrode active material layer 32P and negative electrode active material layer 32N on the positive and negative electrode sheets 35P and 35N, respectively.

[0023] Furthermore, in the secondary battery 1 of this embodiment, the positive and negative electrode sheets 35P, 35N are each shaped into a belt-like shape. The electrode body 10 of this embodiment is configured such that the positive and negative electrode sheets 35P, 35N, which are stacked with the separator 5 sandwiched therebetween, are wound around a winding axis L that extends in the width direction of the belt-like shape (the left-right direction in FIG. 2).

[0024] 2, the separator 5 and each electrode sheet 35 are wound in such a manner that the electrode sheet 35P constituting the positive electrode 3 is wound inward. However, this figure is one example showing the structure of the electrode body 10, and the separator 5 and each electrode sheet 35 may be wound in such a manner that the electrode sheet 35N constituting the negative electrode 4 is wound inward. This determines whether the electrode sheet 35 arranged on the outermost shell of the electrode body 10 is the electrode sheet 35P constituting the positive electrode 3 or the electrode sheet 35N constituting the negative electrode 4.

[0025] 1 to 3, the cover member 22 of the case 20 is provided with a positive electrode terminal 38P and a negative electrode terminal 38N that protrude to the outside of the case 20. Furthermore, each electrode sheet 35 has an uncoated portion 39 in which the electrode active material layer 32 is not formed on the current collector 31. The secondary battery 1 of this embodiment is configured such that the electrode sheet 35P constituting the positive electrode 3 and the positive electrode terminal 38P are electrically connected, and the electrode sheet 35N constituting the negative electrode 4 and the negative electrode terminal 38N are electrically connected, utilizing the uncoated portion 39.

[0026] Specifically, the electrode body 10 of this embodiment is housed in the case 20 with its winding axis L aligned along the longitudinal direction (left-right direction in FIG. 1) of the cover member 22, which is an elongated, generally rectangular plate. Furthermore, in this state, an uncoated portion 39P of an electrode sheet 35P constituting the positive electrode 3 is connected to a positive electrode terminal 38P via a connecting member 40P. Similarly, an uncoated portion 39N of an electrode sheet 35N constituting the negative electrode 4 is connected to a negative electrode terminal 38N via a connecting member 40N.

[0027] Furthermore, an electrolyte solution 41 is poured into the case 20. In the secondary battery 1 of this embodiment, a fluorine-based electrolyte solution 41 in which a lithium salt serving as a supporting salt is dissolved in an organic solvent is used. Thus, the secondary battery 1 of this embodiment is configured such that the electrolyte solution 41 is impregnated into the electrode body 10 sealed in the case 20.

[0028] (electrode composite material) Next, an electrode mixture used in forming the secondary battery 1 of this embodiment will be described. As shown in Figs. 4 and 5, in the secondary battery 1 of this embodiment, the electrode mixture 50 used to form the electrode body 10, more specifically, the positive electrode active material layer 32P to be the positive electrode 3, contains carbon nanotubes (CNTs) as conductive fibrous carbon materials 51. That is, as described above, the electrode mixture 50 is applied to the positive electrode current collector 31P in the state of a mixture paste 37P (see Fig. 2). In addition, in the electrode mixture 50 of this embodiment, the carbon nanotubes (CNTs) are contained in the electrode mixture 50 in a state where they are dispersed in the electrode mixture 50. The electrode mixture 50 of this embodiment is configured such that the carbon nanotubes (CNTs) form a conductive path for the electrode active material 60 located nearby, that is, the positive electrode active material 61 which is the electrode active material 60 for the positive electrode 3.

[0029] In the electrode mixture 50 of this embodiment, the minimum division unit (aggregate) of the lithium transition metal oxide aggregate is used as the primary particle, and the secondary particle obtained by aggregating the primary particle, that is, the particle aggregate (agglomerate), is used for the positive electrode active material 61. The carbon nanotubes CNT are dispersed in the electrode mixture 50 in a manner that they are attached to the surface of the secondary particle.

[0030] 6 and 7, the electrode mixture 50 of this embodiment contains inorganic nanoparticles 70 arranged in a state of being attached to the surface 60s of the electrode active material 60. In FIG. 6, the "broken line enclosure" shown in the figure is the inorganic nanoparticles 70 attached to the surface 60s of the electrode active material 60. Thus, the electrode mixture 50 of this embodiment is configured to suppress the aggregation of the fibrous carbon nanotubes CNT and enhance their dispersibility.

[0031] 8 to 11, in an electrode mixture 50B that does not include such inorganic nanoparticles 70, even if carbon nanotubes (CNTs) are blended, the carbon nanotubes (CNTs) in the electrode mixture 50B tend to aggregate and form clumps. As a result, the carbon nanotubes (CNTs) in the electrode mixture 50B are arranged locally, and thus may not be able to effectively form a conductive path for the electrode active material 60.

[0032] However, as shown in FIG. 7, in the electrode mixture 50 of this embodiment, a plurality of inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 are attached to the carbon nanotubes (CNT) contained in the electrode mixture 50. That is, the inorganic nanoparticles 70 have the characteristic that they are easily attached to the carbon nanotubes (CNT) located nearby due to their intermolecular force. Furthermore, in the electrode mixture 50 of this embodiment, by arranging the inorganic nanoparticles 70 on the surface 60s of the electrode active material 60, a state in which a plurality of attachment points with the inorganic nanoparticles 70 are formed for one carbon nanotube (CNT) can be created. And, in the electrode mixture 50 of this embodiment, the carbon nanotubes (CNT) contained in the electrode mixture 50 are dispersed in an elongated state without being aggregated into a mass, so that the conductive path of the electrode active material 60 can be effectively formed.

[0033] More specifically, in the electrode mixture 50 of this embodiment, the inorganic nanoparticles 70 may be, for example, alumina or lithium tungstate. The particle size of the inorganic nanoparticles 70 may be, for example, one having an average diameter of 25 nm or more and 150 nm or less. The content of the inorganic nanoparticles 70 contained in the electrode mixture 50 is preferably set to an amount represented by the following formula, where the content of the inorganic nanoparticles 70 is "y" and the average diameter of the inorganic nanoparticles 70 is "x" when expressed in weight percent (wt%).

[0034] y≦0.0106x-0.0033 (1) That is, from the viewpoint of forming a plurality of "attachment points" between one carbon nanotube CNT and stretching the carbon nanotube CNT, it is advantageous that many inorganic nanoparticles 70 are present in the electrode mixture 50 and that these inorganic nanoparticles 70 are close to each other. However, if the surface 60s of the electrode active material 60 is covered with these inorganic nanoparticles 70, the battery reaction may be suppressed.

[0035] In consideration of this, the above formula (1) is designed to calculate a suitable content of the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 at which the inorganic nanoparticles 70 are unlikely to suppress the battery reaction. In other words, by setting the content calculated using this formula (1), it is possible to create a state in which the inorganic nanoparticles 70 effectively form a conductive path for the electrode active material 60 while avoiding the suppression of the battery reaction due to the inclusion of the inorganic nanoparticles 70 as described above.

[0036] In addition, regarding the suppression of the battery reaction by the inorganic nanoparticles 70 covering the surface 60s of the electrode active material 60, for example, when the surface 60s of the electrode active material 60 is covered with the inorganic nanoparticles 70 by 10% or more, the decrease in the battery output due to the increase in the reaction resistance becomes significant. In consideration of this point, the above formula (1) is designed to calculate the content of the inorganic nanoparticles 70 contained in the electrode mixture 50 so that the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 do not cover 10% or more of the surface 60s of the electrode active material 60. Thus, the electrode mixture 50 of this embodiment is configured to effectively improve its battery performance by containing the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60.

[0037] More specifically, it is preferable to use carbon nanotubes CNT having an average length of, for example, 100 nm or more and 1000 nm or less. That is, if the length of the carbon nanotube CNT is too short, sufficient conductivity cannot be obtained. On the other hand, if the length of the carbon nanotube CNT is too long, the carbon nanotube CNT may aggregate with each other due to intermolecular forces and hydrogen bonds. As a result, in this case as well, there is a risk that sufficient conductivity cannot be obtained.

[0038] In addition, regarding the diameter of the carbon nanotubes CNT, it is preferable to use those having an average diameter of, for example, 1 nm or more and 100 nm or less. That is, if the diameter of the carbon nano tubes CNT is too thin, the probability of the carbon nano tubes CNT adhering to the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 decreases. Also, if the diameter of the carbon nano tubes CNT is too thick, the probability of them adhering to each other decreases.

[0039] The amount of carbon nanotubes (CNT) contained in the electrode mixture 50 can be set to, for example, 0.5 wt% or more and 2.0 wt% or less. In this case, the ratio of inorganic nanoparticles 70 / carbon nanotubes (CNT) is preferably 0.1 or more and 0.7 or less.

[0040] That is, when the ratio of inorganic nanoparticles 70 / carbon nanotubes (CNT) is small, that is, when the content of inorganic nanoparticles 70 is too small relative to the content of carbon nanotubes (CNT), the probability of these nanoparticles adhering to each other decreases in the electrode mixture 50. And, when the ratio of inorganic nanoparticles 70 / carbon nanotubes (CNT) is too large, that is, when the content of inorganic nanoparticles 70 is too large relative to the content of carbon nanotubes (CNT), as described above, the excess inorganic nanoparticles 70 may suppress the battery reaction.

[0041] Moreover, the diameter ratio of the inorganic nanoparticles 70 to the carbon nanotubes CNT contained in the electrode mixture 50 is preferably, for example, not less than 1.1 and not more than 3.5. That is, when the diameter ratio of the inorganic nanoparticles 70 / carbon nanotubes (CNT) is too small, that is, when the particle size of the inorganic nanoparticles 70 is too small compared to the diameter of the carbon nanotubes (CNT), the probability of them adhering to each other in the electrode mixture 50 decreases. Also, when the diameter ratio of the inorganic nanoparticles 70 / carbon nanotubes (CNT) is too large, that is, when the particle size of the inorganic nanoparticles 70 is too large compared to the diameter of the carbon nanotubes (CNT), the probability of them adhering to each other in the electrode mixture 50 decreases.

[0042] As described above, the electrode mixture 50 of the present embodiment can be embodied by arbitrarily combining the above-mentioned technical features related to the inorganic nanoparticles 70 and the carbon nanotubes CNT used in preparing the electrode mixture 50.

[0043] In particular, it is preferable to combine the "particle size" of the inorganic nanoparticles 70, the above formula (1) that calculates the suitable content of the inorganic nanoparticles 70 according to the average diameter, and the suitable ranges for the "quantity ratio" and "diameter ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT. This can improve the battery performance more effectively by the synergistic effect.

[0044] (action) Next, the operation of this embodiment will be described. That is, the carbon nanotubes CNT in the electrode mixture 50 are stretched by the adhesion of the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 to the carbon nanotubes CNT in the electrode mixture 50. As a result, the aggregation of the carbon nanotubes CNT contained in the electrode mixture 50 is suppressed.

[0045] Next, the effects of this embodiment will be described. (1) The electrode mixture 50 contains an electrode active material 60 and carbon nanotubes CNT as a conductive fibrous carbon material 51. The electrode mixture 50 is configured including inorganic nanoparticles 70 arranged on a surface 60s of the electrode active material 60.

[0046] According to the above-mentioned configuration, the carbon nanotubes (CNTs) in the electrode mixture 50 are dispersed in an elongated state without being aggregated into lumps. As a result, the carbon nanotubes (CNTs) effectively form the conductive paths of the electrode active material 60, thereby ensuring excellent battery performance.

[0047] (2) The average diameter of the inorganic nanoparticles 70 is 25 nm or more and 150 nm or less. According to the above-mentioned configuration, the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 are easily attached to the carbon nanotubes CNT contained in the electrode mixture 50. This makes it possible to create a state in which the carbon nanotubes CNT in the electrode mixture 50 effectively form a conductive path for the electrode active material 60 located in the vicinity thereof.

[0048] (3) The content of inorganic nanoparticles 70 contained in electrode mixture 50, when expressed in weight percent (wt%), is expressed by the above formula (1), where the content of inorganic nanoparticles 70 is “y” and the average diameter of inorganic nanoparticles 70 is “x”.

[0049] That is, by setting the content calculated using the above formula (1), it is possible to avoid a state in which the inorganic nanoparticles 70 covering the surface 60s of the electrode active material 60 suppress the battery reaction. In addition, it is possible to create a state in which the inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 effectively form a conductive path for the electrode active material 60 located in the vicinity thereof. This makes it possible to more effectively improve the battery performance.

[0050] (4) The content of carbon nanotubes (CNT) contained in the electrode mixture (50) is 0.5 wt % or more and 2.0 wt % or less, and the ratio of inorganic nanoparticles (70) to carbon nanotubes (CNT) is 0.1 or more and 0.7 or less.

[0051] According to the above-mentioned configuration, the ratio of the content of the inorganic nanoparticles 70 to the content of the carbon nanotubes CNT can be suitably set. This makes it possible to efficiently create a state in which the carbon nanotubes CNT and the inorganic nanoparticles 70 adhere to each other in the electrode mixture 50, and to avoid a state in which excess inorganic nanoparticles 70 inhibit the battery reaction. As a result, the battery performance can be improved more effectively.

[0052] (5) The diameter ratio of inorganic nanoparticles 70 to carbon nanotubes CNT is 1.1 or more and 3.5 or less. According to the above-mentioned configuration, the ratio of the particle size of the inorganic nanoparticles 70 to the diameter of the carbon nanotubes CNT can be suitably set. This makes it possible to create a state in which the carbon nanotubes CNT and the inorganic nanoparticles 70 are efficiently attached to each other in the electrode mixture 50. As a result, the battery performance can be improved more effectively.

[0053] The above embodiment can be modified as follows: The above embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs.

[0054] In the above embodiment, carbon nanotubes (CNT) are used as the conductive fibrous carbon material 51. However, the present invention is not limited to this, and may be changed arbitrarily as long as it is a fibrous carbon material having conductivity, such as carbon nanofibers (CNF), and is capable of forming a conductive path for the electrode active material 60 located nearby in the electrode mixture 50.

[0055] The inorganic nanoparticles 70 may be any of a structure containing alumina, a structure containing lithium tungstate, and a structure containing both alumina and lithium tungstate. In addition, a substance other than these may be used for the inorganic nanoparticles 70.

[0056] In addition, other substances that can be used as the inorganic nanoparticles 70 to be disposed on the surface 60s of the electrode active material 60 include, for example, metal oxides such as zirconium oxide, titanium oxide, niobium oxide, molybdenum oxide, magnesium oxide, and tungsten oxide. Also, fluorides such as aluminum fluoride and lithium fluoride, or lithium nickel oxide and lithium cobalt oxide can be used. However, it is preferable that the inorganic nanoparticles 70 have a particle size sufficiently smaller than that of the electrode active material 60, and are in a state where a plurality of particles can adhere to the carbon nanotubes CNT in the electrode mixture 50.

[0057] The configuration of the base electrode mixture 50 is arbitrary. For example, the composition of the lithium transition metal oxide forming the electrode active material 60 is arbitrary. In addition, the primary particle diameter and secondary particle diameter are also arbitrary. Furthermore, the type and physical properties of the binder to be mixed in the electrode mixture 50, and the presence or absence of additives are also arbitrary. And, for example, the electrode mixture 50 may be applied to a configuration in which the electrode active material 60 is supported only by the conductive fibrous carbon material 51 without using a general binder.

[0058] The particle size and content of the inorganic nanoparticles 70 in the electrode mixture 50, as well as the length, diameter, and content of the carbon nanotubes CNT in the electrode mixture 50 may be set arbitrarily. The "quantity ratio" and "diameter ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT may also be set arbitrarily. That is, the numerical ranges and calculation formulas described in the above embodiment are preferred examples, and are not necessarily limited to these. For example, they may be set arbitrarily according to the configuration of the electrode mixture 50 that serves as the base as described above, for example, the type and physical properties of the binder, or the presence or absence of the binder, and further the specifications of the electrode active material 60.

[0059] In the above embodiment, the electrode mixture 50 is embodied as a positive electrode mixture used to form the positive electrode active material layer 32P. However, the present invention is not limited thereto, and may be embodied as a negative electrode mixture 50 used to form the negative electrode active material layer 32N, as long as the electrode mixture 50 contains particulate electrode active material 60 and conductive fibrous carbon material 51, as well as inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60.

[0060] In the above embodiment, the electrode mixture 50 is embodied to be used for forming the secondary battery 1 having a configuration as a lithium ion secondary battery. However, the present invention is not limited to this, and may be applied to a secondary battery 1 other than a lithium ion secondary battery.

[0061] The terminal shapes of the positive electrode terminal 38P and the negative electrode terminal 38N are not limited to the shapes shown in Fig. 1 and may be changed as desired. The shape of the case 20 that defines the outer shape of the secondary battery 1 is also not necessarily limited to a flat rectangular box shape and may be changed as desired, for example, to a cylindrical shape. EXAMPLES

[0062] Examples will be described below to more specifically explain the configuration and effects of the present invention, but the present invention is not limited to these examples. <Ratio of inorganic nanoparticles 70 / carbon nanotubes CNT> 12 and 13 are a table and a graph showing the test results on the effect of improving battery performance by including inorganic nanoparticles 70 and the "quantity ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT. Alumina particles were used as the inorganic nanoparticles 70.

[0063] In addition, the "penetration resistance ratio" in each figure is a ratio of the test result of each embodiment to the test result of the comparative example, which is a reference, in the so-called "plate penetration resistance test" performed on the electrode sheet 35 formed using the electrode composite 50, assuming that the test result is "100". In other words, the smaller the value of the "plate penetration resistance test", the better the battery performance. Therefore, the smaller the "penetration resistance ratio" value, the better the battery performance.

[0064] 12 and 13, in "Example 1" to "Example 3" and "Comparative Example 1" which is the reference for the "penetration resistance ratio", the content of carbon nanotubes (CNT) contained in the electrode mixture 50 is "0.8 wt%". In addition, "Comparative Example 1" does not contain inorganic nanoparticles 70 in the electrode mixture 50. The "quantity ratio" of inorganic nanoparticles 70 / carbon nanotubes (CNT) in "Example 1" to "Example 3" is "0.15", "0.20", and "0.11", respectively.

[0065] Under the above conditions, the "penetration resistance ratios" of "Example 1" to "Example 3" were "29.9", "23.7", and "35.2", respectively, all of which were lower than the reference "Comparative Example 1". This result suggests that the inclusion of inorganic nanoparticles 70 arranged on the surface 60s of the electrode active material 60 in the electrode mixture 50 improves the battery performance.

[0066] In addition, the "penetration resistance ratio" increases in the order of "Example 3", "Example 1", and "Example 2" in which the "quantitative ratio" of inorganic nanoparticles 70 / carbon nanotubes (CNT) is low. In other words, as the "quantitative ratio" of inorganic nanoparticles 70 / carbon nanotubes (CNT) decreases, the improvement from "Comparative Example 1" not including inorganic nanoparticles 70 decreases. Based on this tendency, it is considered preferable to set the lower limit of the "quantitative ratio" of inorganic nanoparticles 70 / carbon nanotubes (CNT) to, for example, 0.1 or more.

[0067] 13, it is presumed that in the region where the "quantity ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT is lower than "0.1", the "penetration resistance ratio" value increases linearly as the "quantity ratio" decreases. Therefore, it is also possible to set the lower limit of the "quantity ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT to, for example, "0.07 or more" or "0.05 or more".

[0068] The upper limit of the "quantity ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT can be derived using formula (1) shown in the above embodiment. For example, if the average diameter of the inorganic nanoparticles 70 is "x=50 nm", the preferable content of the inorganic nanoparticles 70 contained in the electrode mixture 50 is derived as "0.53 wt% or less" from formula (1). Furthermore, as in the above examples and comparative examples, if the content of the carbon nanotubes CNT contained in the electrode mixture 50 is "0.8 wt%, "the "quantity ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT is about "0.66". This makes it possible to confirm that the upper limit of the "quantity ratio" shown in the above embodiment, "0.7 or less", is appropriate.

[0069] <Diameter ratio of inorganic nanoparticles 70 / carbon nanotubes CNT> 14 and 15 are a table and a graph showing the test results regarding the "diameter ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT.

[0070] Alumina particles were used for the inorganic nanoparticles 70. In addition, in "Example 4" to "Example 6" and "Comparative Example 2" and "Comparative Example 3", the content of carbon nanotubes (CNT) contained in the electrode mixture 50 was "0.8 wt%". The "quantity ratio" of inorganic nanoparticles 70 / carbon nanotubes (CNT) was adjusted to be "0.15". In each figure, the value of the "penetration resistance ratio" represents the ratio when the test result of "Comparative Example 2" is set to "100".

[0071] As shown in FIG. 14 and FIG. 15, the diameters (nm) of the carbon nanotubes CNT in "Example 4" to "Example 6" and "Comparative Example 2" and "Comparative Example 3" are "31.3", "43.8", "43.8", "56.3", and "43.8" from the left in FIG. 14, respectively. In addition, in each of these examples and comparative examples, the lengths (nm) of the carbon nanotubes CNT are "729", "805", "957", "601", and "957" from the left in the same figure, respectively. Furthermore, in each of these examples and comparative examples, the particle diameters of the inorganic nanoparticles 70 are "50 nm" in "Example 4", "Example 5", and "Comparative Example 2", "150 nm" in "Example 5", and "200 nm" in "Comparative Example 3". As a result, in each of these examples and comparative examples, the "diameter ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT is, from left to right in the figure, "1.60," "1.14," "3.43," "0.889," and "4.57," respectively.

[0072] Under the above conditions, the "penetration resistance ratios" of "Example 4" to "Example 6" were "1.9", "8.7", and "17.3", respectively, all lower than the standard "Comparative Example 2". However, in "Comparative Example 3", the "penetration resistance ratio" was only "61.7". From this tendency, it is considered preferable to set the lower limit of the "diameter ratio" of the inorganic nanoparticles 70 / carbon nanotubes CNT to, for example, "1.1 or more". It is also considered preferable to set the upper limit to, for example, "3.5 or less". And, from this test result, it can be confirmed that the preferable setting range for the "diameter ratio" shown in the above embodiment, "1.1 or more, 3.5 or less", is appropriate.

[0073] It is presumed from the plot in FIG. 15 that in the region where the "diameter ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT is higher than approximately "3.0", the value of the "penetration resistance ratio" increases linearly as the "diameter ratio" increases. Therefore, it is considered more preferable to set the upper limit of the "diameter ratio" of inorganic nanoparticles 70 / carbon nanotubes CNT to, for example, "3.4 or less" or "3.0 or less". It is also considered possible to extend the lower limit of this "diameter ratio" to, for example, about "4.0 or less". [Explanation of symbols]

[0074] 50…Electrode composite material 51...Conductive fibrous carbon material 60...electrode active material 60s…Surface 70…Inorganic nanoparticles CNT: Carbon nanotube

Claims

1. A positive electrode mixture containing a lithium transition metal oxide and a conductive fibrous carbon material as an electrode active material and containing inorganic nanoparticles arranged on a surface of the electrode active material, a diameter ratio of the inorganic nanoparticles to the conductive fibrous carbon material is 1.1 or more and 3.5 or less; The inorganic nanoparticles include at least one of alumina and lithium tungstate, The average diameter of the inorganic nanoparticles is 25 nm or more and 150 nm or less. Positive electrode mixture.

2. When the content of the inorganic nanoparticles contained in the electrode mixture of the positive electrode is expressed in weight percent, The content of the inorganic nanoparticles is "y", The average diameter of the inorganic nanoparticles is represented by "x", and the formula is y≦0.0106x-0.0033 The positive electrode mixture according to claim 1 ,

3. The content of the conductive fibrous carbon material contained in the electrode mixture of the positive electrode is 0.5 wt % or more and 2.0 wt % or less, The ratio of the inorganic nanoparticles to the conductive fibrous carbon material is 0.1 or more and 0.7 or less. The electrode mixture for a positive electrode according to claim 1 or 2.

4. The conductive fibrous carbon material is a carbon nanotube. The positive electrode mixture according to any one of claims 1 to 3.

5. A secondary battery formed using the positive electrode mixture according to any one of claims 1 to 4.

6. A secondary battery formed using a positive electrode mixture containing a lithium transition metal oxide and a conductive fibrous carbon material as an electrode active material, The electrode mixture of the positive electrode includes inorganic nanoparticles disposed on a surface of the electrode active material, The average diameter of the inorganic nanoparticles is 25 nm or more and 150 nm or less; When the content of the inorganic nanoparticles contained in the electrode mixture of the positive electrode is expressed in weight percent, The content of the inorganic nanoparticles is "y", The average diameter of the inorganic nanoparticles is represented by "x", and the formula is y≦0.0106x-0.0033 As well as being expressed in The content of the conductive fibrous carbon material contained in the electrode mixture of the positive electrode is 0.5 wt % or more and 2.0 wt % or less, The ratio of the inorganic nanoparticles to the conductive fibrous carbon material is 0.1 or more and 0.7 or less, The diameter ratio of the inorganic nanoparticles to the conductive fibrous carbon material is 1.1 or more and 3.5 or less. Secondary battery.

Citation Information

Patent Citations

  • Carbon nanotube key joint lithium iron phosphate composite electrode material and preparation method thereof

    CN101442126A

  • Negative electrode for non-aqueous electrolyte secondary battery, its manufacturing method, and non-aqueous secondary battery

    JP2008041465A

  • Battery electrode doubling as current collector, and battery having the same

    JP2016031922A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery

    JP2018032543A

  • High-nickel cathode material for lithium-ion batteries coated with modified superhydrophobic material and method for preparing the same.

    JP2018533174A